2023
DOI: 10.1108/jiabr-05-2021-0151
|View full text |Cite
|
Sign up to set email alerts
|

Zakat administration reformation towards an effective and efficient zakat revenue generation

Abstract: Purpose This study aims to identify the inputs from zakat administrators and experts needed for more efficient and effective zakat revenue generation. Design/methodology/approach Face-to-face interviews with zakat executives, administrators and experts are conducted to collect data. Findings The findings show three components of input required in the zakat transformation: environment, resources and history. The environmental component comprises five sub-components: companies, banks, zakat recipients, indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 63 publications
0
3
0
1
Order By: Relevance
“…Consequently, understanding why Muslim communities select Sharia-based financial products and services through banks is vital to generate Sharia-compliant client behaviours (Bin-Nashwan et al , 2021). To ensure customer adherence to Sharia rules, it is essential to consider environmental factors, such as Islamic bank institutions, individual or institutional consumer attitudes and Islamic bank assets (Saad et al , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, understanding why Muslim communities select Sharia-based financial products and services through banks is vital to generate Sharia-compliant client behaviours (Bin-Nashwan et al , 2021). To ensure customer adherence to Sharia rules, it is essential to consider environmental factors, such as Islamic bank institutions, individual or institutional consumer attitudes and Islamic bank assets (Saad et al , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is little evidence of study focusing on investigating Islamic bank customers’ that adherence to Sharia compliance. Saad et al (2023) found a model to increase zakat compliance as income increased. Sadallah et al (2023) found that knowledge and political instability significantly affected businessmen’s zakat compliance, while service quality and trust had no significant effect on businessmen’s zakat compliance.…”
Section: Introductionmentioning
confidence: 99%
“…A business model is viewed by organisation theory as an abstract depiction of the organisation's structure or design (Saad et al, 2023). The business model's functions are to comprehend the essential workings of an established organisation more thoroughly, to serve as a foundation for enhancing the present business operations and structure, to display a company's innovative structure, to test out a novel business idea, or to imitate or research a strategy employed by a rival firm (e.g., benchmarking on the model level), also to locate outsourcing possibilities.…”
Section: Business Modelmentioning
confidence: 99%
“…The questionnaire was answered, and the average score is 71, which means that IZI in the Collaborators segment is based on Figure 2. The characteristics of collaborators are breaking down traditional silos; the strategy that needs to apply is to use digital to create a competitive advantage, and the top critical marketing priority over the next 12 months is to build digital awareness (Saad et al, 2023). To build digital into a competitive differentiator, Collaborators should: 1.…”
Section: ) Readiness Analysismentioning
confidence: 99%
“…It involves using digital platforms, applications, and databases to facilitate Zakat transactions, enable efficient data management of Zakat recipients (mustahik), and enhance transparency in Zakat administration (Mutamimah et al, 2021). By leveraging technology, digital Zakat management aims to improve accessibility, accuracy, and efficiency in handling Zakat funds, ensuring they are promptly disbursed to the intended beneficiaries (Saad et al, 2023). Digital Zakat Management, Zakat Management Accountability, and Zakat Growth Acceleration are intertwined elements that collectively contribute to the success and impact of Zakat in society.…”
Section: Introductionmentioning
confidence: 99%